The Effectiveness of a Pneumatic Compression Belt in Reducing Respiratory Motion of Abdominal Tumors in Patients Undergoing Stereotactic Body Radiotherapy. (June 2014) - Lovelock, D. Michael; Zatcky, Joan; Goodman, Karyn; Yamada, Yoshiya
Purpose: Abdominal compression using a pneumatic abdominal compression belt developed in-house has been used to reduce respiratory motion of patients undergoing hypofractionated or single fraction stereotactic radio-ablative therapy for abdominal cancers. The clinical objective of belt usage was to reduce the cranial-caudal (CC) respiratory motion of the tumor to 5 mm or less during both CT simulation and treatment. A retrospective analysis was done to determine the effectiveness of the device and associated clinical procedures to reduce the CC respiratory motion of the tumor.Materials and Methods: 42 patients treated for tumors in the liver (30), adrenal glands (6), pancreas (3) and lymph nodes (3) using high dose hypofractionated radiotherapy between 2004 and the present were eligible for analysis. All patients had 2–3 radiopaque fiducial markers implanted near the tumor prior to simulation, or had clips from prior surgery. Integral to the belt is an inflatable air bladder that is positioned over the abdomen. The pneumatic pressure was set to a level in consultation with the patient. The CC motion was measured fluoroscopically with and without pneumatic pressure. Pneumatic pressure was used at all treatments to reduce to CC motion to that achieved at simulation.Results: The mean CC motion with the belt in place, but no additional air pressure was 11.4 mm with a range of 5–20 mm. With the pressure applied, the mean CC motion was reduced to 4.4 mm with a range of 1–8 mm ( P -value < 0.001). The clinical objective of reducing the CC motion of the tumor to a maximum excursion of 5 mm or less was achieved in 93% of cases.Conclusion: The use of a pneumatic compression belt and associated clinical procedures was found to result in a significant and frequently substantial reduction in the CC motion of the tumor.